Shifting Biological Drivers Govern Drought and Wetting Legacies on Soil Respiration - Yanan Cui; Stefano Manzoni; Zhiyuan Quan; Daiqi Zhao; Lina Yan; Chengliang Wang; Jidong Liao; Jiancheng Yu; Yuting Liu; Yanan Li; Wei Sun; Baoku Shi (Global Change Biology, 2026)
Climate change is intensifying precipitation extremes, yet how historical drought and wetting shape post‐event soil carbon fluxes remains poorly understood. Using a seven‐year precipitation manipulation experiment (−70% to +50%) followed by a two‐year recovery period in a semi‐arid grassland, we quantified legacy effects on soil respiration (Rs) and its autotrophic (Ra) and heterotrophic (Rh) components. Historical moderate wetting (+30%) generated the strongest positive legacy, increasing Rs, Rh, and Ra by 21.9%, 24.4%, and 26.9%, respectively, during the first recovery year. In contrast, historical drought treatments (−70% to −30%) produced biphasic legacies, characterized by early‐season suppression followed by later‐season positive responses, potentially associated with decomposition of drought‐accumulated substrates and vegetation recovery. Ra generally showed stronger recovery responses than Rh, indicating contrasting sensitivities of plant‐ and microbially ‐ derived respiration to moisture and carbon availability. The dominant controls of respiration also shifted over time: first‐year legacies were associated mainly with microbial carbon substrates and extracellular enzyme activities, whereas second‐year responses were increasingly linked to plant allocation strategy and microbial community composition. Despite these contrasting trajectories, Rs, Ra, and Rh largely converged to control levels within two years. Our results demonstrate that precipitation legacies in semi‐arid grasslands are asymmetric and temporally dynamic, with important implications for predicting carbon cycling under increasing hydrological variability.